Variations on A-Browder-Type Theorems - Berkani, Mohammed; Kachad, Mohammed; Zariouh, Hassan; Zguitti, Hassane (Sarajevo Journal of Mathematics, 2024)
We introduce and we study the new spectral properties $(SBw)$, $(SBaw)$, $(SBab)$ and $(SBb).$ Among other results, we show that if $T$ is a bounded linear operator acting on a Banach space $X$, then $T$ possesses property $(SBb)$ if and only if $T$ possesses property $(b)$ and $Π^0(T)=Π_a(T).$ 2010 Mathematics Subject Classification. Primary 47A53, 47A10, 47A11.